The Relationship Between Stunting Incidents in Toddlers and the Level of Mother's Education and Family Parenting Patterns in Sitinjuau Laut District - Novinovrita. M, Novinovrita. M; Rasmita, Rasmita (Civiliza Publishing, Indonesia., 2025)
A single paragraph of about 250 words maximum. For Stunting is a growth disorder in children where their height is below the standard for their age. Although the prevalence of stunting in Indonesia has decreased, it remains high according to WHO criteria. Stunting has the potential to reduce productivity in adulthood and increase the risk of degenerative diseases. The causes of stunting are complex and varied. This study aims to determine the relationship between maternal education level, nutritional intake, and family parenting on the incidence of stunting in children under five in the working area of Puskesmas Hiang, Kerinci Regency. This research used a quantitative method with a cross-sectional design. Data collection was conducted from March to May 2024. The study population consisted of 837 children under five, with a sample of 94 children selected using proportional random sampling. The independent variables in this study included “maternal education level, nutritional intake, and family parenting,” while the dependent variable was “stunting.” Data analysis was conducted using the Chi-Square test. The prevalence of stunting in children under five reached 23.4%. A significant relationship was found between maternal education level and nutritional intake (energy, carbohydrates, vitamin A, and fat) with the incidence of stunting in children under five. However, there was no significant relationship between protein intake, zinc intake, and family parenting with stunting incidence. Maternal education level, are related to stunting in children under five in the working area of Puskesmas Hiang, Kerinci Regency.